Meta-analysis of flavonoids use into beef and dairy cattle diet: Performance, antioxidant status, ruminal fermentation, meat quality, and milk composition - Orzuna-Orzuna, José Felipe; Dorantes-Iturbide, Griselda; Lara-Bueno, Alejandro; Chay-Canul, Alfonso Juventino; Miranda-Romero, Luis Alberto; Mendoza-Martínez, Germán David (Frontiers in Veterinary Science, 2023)
The objective of this study was to evaluate the effects of dietary supplementation with flavonoids (FLAs) on animal performance, digestibility, antioxidant status in blood serum, rumen parameters, meat quality, and milk composition derived from beef and dairy cattle through a meta-analysis. Thirty-six peer-reviewed publications were included in the data set. The weighted mean differences (WMD) between the FLAs treatments and the control treatment were used to assess the effect size. Dietary supplementation with FLAs decreased feed conversion ratio (WMD = -0.340 kg/kg; p = 0.050) and increased (p < 0.05) dry matter intake (WMD = 0.191 kg/d), dry matter digestibility (WMD = 15.283 g/kg of DM), and daily weight gain (WMD = 0.061 kg/d). In blood serum, FLAs supplementation decreased the serum concentration of malondialdehyde (WMD = -0.779 nmol/mL; p < 0.001) and increased (p < 0.01) the serum concentration of superoxide dismutase (WMD = 8.516 U/mL), glutathione peroxidase (WMD = 12,400 U/mL) and total antioxidant capacity (WMD = 0.771 U/mL). A higher ruminal propionate concentration (WMD = 0.926 mol/100 mol; p = 008) was observed in response to FLAs supplementation. In meat, the dietary inclusion of FLAs decreased (p < 0.05) shear force (WMD = -1.018 kgf/cm2), malondialdehyde content (WMD = -0.080 mg/kg of meat), and yellowness (WMD = -0.460). Supplementation with FLAs decreased milk somatic cell count (WMD = -0.251 ×103 cells/mL; p < 0.001) and increased (p < 0.01) milk production (WMD = 1.348 kg/d), milk protein content (WMD = 0.080 g/100 g) and milk fat content (WMD = 0.142 g/100 g). In conclusion, dietary supplementation with FLAs improves animal performance and nutrient digestibility in cattle. In addition, FLAs improve the antioxidant status in blood serum and the quality of meat and milk.